Trust spillovers in the sharing economy: Does international Airbnb experience foster cross-national trust? - Judith Kas; Joyce Delnoij; Rense Corten; Paolo Parigi (Journal of Consumer Behaviour, 2022)
Sharing economy platforms commonly claim to bring about positive social impacts, such as facilitating contact between individuals that would not have met otherwise. According to contact theory, such intergroup contact would change the stereotypes that individuals hold of outgroup members, such as people with a different nationality or ethnicity. We use a large-scale online Investment Game experiment among Airbnb users to study the effect of Airbnb interactions on cross-national trust. In contrast with common claims about the positive impact of the sharing economy, we did not find that individuals who had prior experience with a nationality as a host or a guest on Airbnb trusted persons of that nationality more. This may be because monetization, institutionalization and professionalization of Airbnb limits the intensity of contact, or because Airbnb mostly establishes contact between individuals with similar backgrounds.
Keywords: 300